Omental lipoma in pediatric age group: clinical presentation, image findings and management - Falsarella,Priscila Mina (2022)
ABSTRACT A 2-year-old female patient, admitted in the emergency room, presented diarrhea for 5 days and bloody stools in the last 24 hours. Physical examination revealed no significant findings. Ultrasound was initially performed, showing an elongated, well delimited and solid mass occupying since right hypocondrium until left iliac fossa, displacing adjacent structures. In sequence, magnetic resonance imaging was performed for confirmation of findings suggestive of omentum lipoma. After 1 week, the surgical resection was performed by videolaparoscopic acess. During 2-year follow-up, there was no sign of recurrence.